A MECHANISM FOR THE FORMATION OF THE MINERALIZED MN DEPOSITS AT MEREHEAD QUARRY, CRANMORE, SOMERSET, ENGLAND - Turner R. (My University, 2006)
Mississippi Valley type galena deposits emplaced into Carboniferous limestones throughout the Mendip Hills during the late Permian or Triassic period were locally exposed to the action of seawater during the Jurassic period following regional uplift and erosion of the intervening strata. Oxidation of galena initiated the deposition of manganate minerals from the seawater, and these adsorbed heavy metals from both the seawater and local environment. A subsequent hydrothermal event heated the lead-manganate deposits causing decomposition of the galena and creating the conditions which led to the formation of the suite of unusual secondary minerals - including a number of rare oxychlorides - now found at Merehead. Heating of the manganate phases converted them to Mn oxides and released the entrained heavy metals which were then incorporated into unusual mineral phases. The impervious Mn oxide coating which enclosed the cooling Pb-rich areas isolated them chemically, leading to closed-system behaviour. The high-T phases at Merehead are similar to those found in the Pb-bearing silicic skarns at Långban, whilst the suite of secondary minerals which evolved in the closed-system environments bears striking similarities to the 'anomalous sequence' of minerals found at the Mammoth-St. Antony Mine. The complexity of these formation processes probably explains the rarity of Mendip-type Pb-Mn deposits. The collective importance of the disconformity, the hydrothermal event, and subsequent sealing of the deposits are recognized for the first time, and the temperature of the hydrothermal event is shown to have been much greater than has heretofore been realized. Silurian volcanic strata underlying the Carboniferous limestones which have previously been assumed to be the source of heavy metals are shown to have been uninvolved in the process. © 2006 The Mineralogical Society.
Keywords: ENGLAND; MENDIP; MEREHEAD; MEREHEADITE; MN DEPOSITS; OXYCHLORIDE; SOMERSET; Jurassic; Triassic; Permian; Carboniferous; Silurian; Mesozoic::Jurassic; Мезозой::Юрская; Mesozoic::Triassic; Мезозой::Триасовая; Paleozoic::Permian; Палеозой::Пермская; Paleozoic::Carboniferous; Палеозой::Каменноугольная; Paleozoic::Silurian; Палеозой::Силурийская